Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lời giải:
$x^6-x^4+x^2-1=x^4(x^2-1)+(x^2-1)=(x^2-1)(x^4+1)$
$=\frac{(x^2-1)(x^2+1)(x^4+1)}{x^2+1}=\frac{(x^4-1)(x^4+1)}{x^2+1}=\frac{x^8-1}{x^2+1}$
để f(x) và g(x) cùng chia hết cho -2x+6
=>\(\hept{\begin{cases}f\left(3\right)=0\\g\left(3\right)=0\end{cases}}\)<=>\(\hept{\begin{cases}\frac{3867}{20}-m+n=0\\\frac{1911}{11}+3m-n=0\end{cases}}\)<=>\(\hept{\begin{cases}-m+n=-\frac{3867}{20}\\3m-n=-\frac{1911}{11}\end{cases}< =>\hept{\begin{cases}m=-183,5386364\\n=-376,8886364\end{cases}}}\)
2) a) \(x^2-3=\left(x-\sqrt{3}\right)\left(x+\sqrt{3}\right)\)
b) \(x^2-6=\left(x-\sqrt{6}\right).\left(x+\sqrt{6}\right)\)
c) = \(x^2+2x.\sqrt{3}+\left(\sqrt{3}\right)^2=\left(x+\sqrt{3}\right)^2\)
d) = \(x^2-2x\sqrt{5}+\left(\sqrt{5}\right)^2=\left(x-\sqrt{5}\right)^2\)
=>(x-\(\sqrt{5}\))2
=>(x-\(\sqrt{5}\)) (x-\(\sqrt{5}\))
Lời giải:
$x^6-x^4+x^2-1=x^4(x^2-1)+(x^2-1)$
$=(x^2-1)(x^4+1)=\frac{(x^2-1)(x^2+1)(x^4+1)}{x^2+1}=\frac{(x^4-1)(x^4+1)}{x^2+1}=\frac{x^8-1}{x^2+1}$